Karakteristik dan Persepsi Pemanfaatan Lahan Pekarangan Untuk Pangan di Daerah Perkotaan Pada Program Pekarangan Pangan Lestari (P2L) di Kota Pontianak - Febian, Rachmad; Sudrajat, Jajat; Fitrianti, Wanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Sustainable Food Yard Program (P2L) is an activity carried out by community groups that jointly work on their yard as a source of food in a sustainable manner to increase availability, accessibility and utilization, as well as income. This study aimed to find out the characteristics of yard cultivation in the program and found that the majority of participants had yards with an area of less than 100 m2 with an average land area of 32.4 m2, and most used polybags to grow vegetables and fruits. Participants' perceptions of the use of their yards went well. This can be proven by the high perception of P2L participants. Of the 7 types of perceptions interviewed, 65 respondents had a high perception score category with an average score of 3.26, which means that P2L participant respondents had a good perception of the P2L program in Pontianak City. The conclusion of this study is that the P2L program in Pontianak City is effective in increasing the availability, accessibility, and use of home gardens as a sustainable food source. The active participation of the community in cultivating their home gardens is an important factor and has a positive impact on income and food sustainability.